A proposed CT contrast agent using carboxybetaine zwitterionic tantalum oxide nanoparticles: Imaging, biological, and physicochemical performance - FitzGerald, Paul F. (Invest Radiol, 2016)
OBJECTIVES: To produce and evaluate a proposed computed tomography (CT) contrast agent based on carboxybetaine zwitterionic (CZ) coated soluble tantalum oxide nanoparticles (CZ-TaO NPs). We chose tantalum to provide superior imaging performance compared to current iodine-based clinical CT contrast agents. We developed the CZ coating to provide biological and physical performance similar to that of current iodinated contrast agents. The aim of this study was to evaluate the imaging, biological, and physicochemical performance of this proposed contrast agent compared to clinically-used iodinated agents. MATERIALS AND METHODS: We evaluated CT imaging performance of our CZ-TaO NPs compared to an iodinated agent in live rats, imaged centrally-located within a tissue-equivalent plastic phantom that simulated a large patient. To evaluate vascular contrast enhancement, we scanned the rats’ great vessels at high temporal resolution during and following contrast agent injection. We performed several in vivo CZ-TaO NP studies in healthy rats to evaluate tolerability. These studies included injecting the agent at the anticipated clinical dose (ACD) and at 3 times and 6 times the ACD, followed by longitudinal hematology to assess impact to blood cells and organ function (from 4 hours to 1 week). Kidney histological analysis was performed 48 hours after injection at 3 times the ACD. We measured the elimination half-life of CZ-TaO NPs from blood, and we monitored acute kidney injury biomarkers with a kidney injury assay using urine collected from 4 hours to 1 week. We measured tantalum retention in individual organs and in the whole carcass 48 hours after injection at ACD. CZ-TaO NPs were synthesized and analyzed in detail. We used multi-dimensional nuclear magnetic resonance (NMR) to determine surface functionality of the nanoparticles. We measured nanoparticle size and solution properties (osmolality and viscosity) of the agent over a range of tantalum concentrations, including the high concentrations required for standard clinical CT imaging. RESULTS: CT imaging studies demonstrated image contrast improvement of approximately 40–50% using CZ-TaO NPs compared with an iodinated agent injected at the same mass concentration. Blood and organ analyses showed no adverse effects following injection in healthy naïve rats at 3 times the ACD. Retention of tantalum at 48 hours after injection was less than 2% of the injected dose in the whole carcass, which very closely matched the reported retention of existing commercial iodine-based contrast agents. Urine analysis of sensitive markers for acute kidney injury showed no responses at 1 week following injection at 3 times the ACD; however, a moderate response in the neutrophil gelatinase-associated lipocalin (NGAL) biomarker was measured at 24 and 48 hours. Compared to other tantalum oxide nanoparticles reported in the literature, CZ-TaO NPs had relatively low osmolality and viscosity at concentrations >200 mg Ta/mL, and were similar in these physical properties to dimeric iodine-based contrast agents. CONCLUSIONS: We found that a CZ-TaO NP-based contrast agent is potentially viable for general-purpose clinical CT imaging. Our results suggest that such an agent can be formulated with clinically-viable physicochemical properties, can be biologically safe and cleared rapidly in urine, and can provide substantially improved image contrast at CT compared to current iodinated agents.